Pengaruh Koneksi Politik, Capital Intensity, Profitabilitas, Leverage dan Ukuran Perusahaan Pada Agresivitas Pajak - Windaswari, Kadek Ayu; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 23 No 3 (2018), 2018)
Tax planning measures either use legal (tax avoidance) or illegal (tax evasion) for the purpose of reduce the tax burden is called tax aggressiveness. The purpose of this study was to analyze the influence of political connections, capital intensity, profitability, leverage, and firm size on tax aggressiveness. The object of this research is the mining sector companies listed on the Indonesia Stock Exchange period 2012-2016. Samples obtained as many as 60 companies by purposive sampling method during the period of 5 years. Data analysis technique used in this research is multiple linear regression analysis. The results of the analysis found that profitability had a negative effect on tax aggressiveness. This shows that the higher profitability of the company will lead to decreased levels of corporate tax aggressiveness because the higher the profitability of the company's performance the better so that the company will be able to pay its tax obligations. Variables of political connection, capital intensity, leverage, and firm size have no effect on tax aggressiveness. Keywords: capital intensity, leverage, political connections, profitability, firm size, tax aggressiveness.